Implementation of Talking Stick Media to Improve Arabic Vocabulary Mastery and Speaking Skills - Auliya, Afra Nada; Smith, Henry (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2024)
Students often consider Arabic language learning challenging due to difficulties in understanding and pronouncing vocabulary and the numerous changes in word forms, making the language seem complex and uninteresting. This issue is exacerbated by passive learning methods focusing solely on memorizing vocabulary without employing strategies to increase student participation and engagement. As a solution, the Talking Stick media was introduced to create a more interactive and engaging learning process to improve students' vocabulary mastery and speaking skills. This study assesses vocabulary mastery and Arabic speaking skills before and after applying the Talking Stick media and evaluates the improvement. The study used a quasi-experimental method with a pre-test and post-test design, adopting a quantitative approach. Data collection techniques included direct observation, interviews, and tests. The results showed that using the Talking Stick media had a positive impact, with students' vocabulary mastery increasing from an average of 51 to 85 and speaking skills improving from 57 to 85. The N-Gain score for vocabulary mastery reached 0.70 and 0.75 for speaking skills, categorized as "high." In contrast, the control group demonstrated only moderate improvements. These findings indicate that the Talking Stick media significantly enhances vocabulary mastery and speaking skills compared to conventional learning methods. Future research is recommended to explore other interactive media for Arabic language teaching.